Comparative histology of mouse, rat, and human pelvic ligaments. Issue 11 (November 2016) - Iwanaga, Ritsuko; Orlicky, David; Arnett, Jameson; Guess, Marsha; Hurt, K.; Connell, Kathleen
Abstract Introduction and hypothesis The uterosacral (USL) and cardinal ligaments (CL) provide support to the uterus and pelvic organs, and the round ligaments (RL) maintain their position in the pelvis. In women with pelvic organ prolapse (POP), the connective tissue, smooth muscle, vasculature, and innervation of the pelvic support structures are altered. Rodents are commonly used animal models for POP research. However, the pelvic ligaments have not been defined in these animals. In this study, we hypothesized that the gross anatomy and histological composition of pelvic ligaments in rodents and humans are similar. Methods We performed an extensive literature search for anatomical and histological descriptions of the pelvic support ligaments in rodents. We also performed anatomical dissections of the pelvis to define anatomical landmarks in relation to the ligaments. In addition, we identified the histological components of the pelvic ligaments and performed quantitative analysis of the smooth muscle bundles and connective tissue of the USL and RL. Results The anatomy of the USL, CL, and RL and their anatomical landmarks are similar in mice, rats, and humans. All species contain the same cellular components and have similar histological architecture. However, the cervical portion of the mouse USL and RL contain more smooth muscle and less connective tissue compared with rat and human ligaments. Conclusion The pelvic support structures of rats and mice are anatomically and histologically similar to those of humans. We propose that both mice and rats are appropriate, cost-effective models for directed studies in POP research.